Las nuevas pantallas, un reto educativo - García Serrano, José Antonio; Moreno Herrero, Isidro (Revista Complutense de Educación, 2006)
The term new media refers to the new mass media, particularly to Internet, video games and mobile phones, which, with the traditional ones, TV and advertising, make up the current information and communication technologies scene. Through the article, several new media are analysed underlining its pros and cons in order to reflect on it, so that all of those people involved in educational processes could use them as referents when it comes to deal with critical analysis of the media, thereby obtaining their own opinions to better tackle education as regards information and communication technologies.